Factors Affecting Library Loyalty in Academic Libraries - Marline G. Roma; Celbert M. Himang (Philippine Social Science Journal, 2025)
Grounded in DeLone and McLean’s Information Systems Success Model, this study examines the drivers of library loyalty among 550 Gen Z students in Cebu City. Using Partial Least Squares Structural Equation Modeling (PLS-SEM), the research found that System and Service Quality positively influence both Intention to Use and User Satisfaction, which are significant predictors of Library Loyalty. While Information Quality significantly affected Satisfaction, AI Chatbot Engagement did not moderate the relationship between quality dimensions and User Satisfaction, suggesting that AI technology does not diminish the perceived value of core library functions. Consequently, the study concludes that to maintain Gen Z patronage, academic libraries must prioritize enhancing their systems, services, and digital resources, while future research should continue to monitor the integration of emerging technologies like AI and virtual reality.